A flying start? Long term consequences of maternal time investments in children during their first year of life - Pedro Carneiro; Katrine V. Loken; Kjell G. Salvanes (Centre for Microdata Methods and Practice (cemmap), 2010)
We study the impact of increasing the time that the mother spends with her child in the first year of her life. In particular, we examine a reform that increased paid and unpaid maternity leave entitlements in Norway. In response to this reform, maternal leave increased on average by 4 months and family income was unaffected. We find that this increase in maternal time with the child led to a 2.7 percentage points decline in high school dropout rates, going up to 5.2 percentage points for those whose mothers have less than 10 years of education. This effect is especially large for children of mothers who, in the absence of the reform, would take very low levels of unpaid leave. Finally, there is a weak impact on college attendance. The results also suggest that much of the impact of early time with the child is at low levels of maternal education.
Keywords: 330; Kinderbetreuung; Mütter; Elternzeit; Humankapital; Kinder; Wirkungsanalyse; Norwegen